Pelatihan Pengembangan Pembelajaran berbasis Entreprenuership bermuatan Kearifan Lokal - Hairida, Hairida; Masriani, Masriani; Enawaty, Eny; Muharini, Rini; Lestari, Ira; Ifriany, Andi; Erlina, Erlina; Sahputra, Rachmat; Ulfah, Maria; Mayasari, Eni; Sasri, Risya; Agusta, Muhammad Farras Leonasa (IKIP PGRI Bojonegoro, 2024)
ABSTRACTImplementing entrepreneurship as part of the Merdeka Curriculum is considered suboptimal due to the numerous challenges schools face. This is consistent with the survey results among chemistry educators in the Singkawang, which showed that while most have implemented entrepreneurship in their teaching, it has not yet incorporated local wisdom and has not been included in their teaching tools. The purpose of this community service program (PKM) is to enhance educators' ability to develop entrepreneurship-based learning that incorporates local wisdom and to describe educators' responses to the training activities conducted. The method used in this PKM is a training method for 24 chemistry educators in Singkawang, consisting of three stages: preparation, implementation, and evaluation. The results of the PKM activities showed increased knowledge and helped Singkawang's chemistry educators integrate these two concepts into their teaching.Keywords: Learning Development, Entreprenuership, Local Wisdom ABSTRAKPelaksanaan kewirausahaan sebagai implementasi kurikulum merdeka dirasa belum optimal dikarenakan terdapat banyak kendala yang harus dihadapi oleh sekolah. Hal tersebut sesuai dengan hasil survei pada pendidik kimia Kota Singkawang yang sebagian besar sudah mengimplementasikan kewirausahaan dalam pembelajarannya akan tetapi belum bermuatan kearifan lokal dan belum dituangkan dalam perangkat pembelajarannya. Tujuan PKM ini ialah untuk meningkatkan kemampuan pendidik dalam mengembangkan pembelajaran yang berbasis entrepreneurship bermuatan kearifan lokal serta untuk mendeskripsikan respon pendidik terhadap kegiatan pelatihan yang dilakukan. Metode yang digunakan pada PKM ini ialah metode pelatihan untuk 24 pendidik kimia Kota Singkawang yang terdiri dari 3 tahap. Tahapan yang dilakukan pada PKM ini ialah tahap persiapan, pelaksanaan dan evaluasi. Hasil kegiatan PKM diketahui dapat meningkatkan pengetahuan dan membantu pendidik kimia Kota Singkawang dalam mengintegrasikan kedua konsep tersebut ke dalam pembelajaran.Kata Kunci: Pengembangan Pembelajaran, Entreprenuership, Kearifan Lokal